Inventory of the Langkat Regency Regional Museum Collection - Siti Aisyah; Nur Sonia Sitompul; Annisa; Anita Syamsinar; Ridho Akbar Fadilah; Hotmatua Paralihan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
A museum is a permanent institution established for the benefit of the public and society, as an institution capable of caring for, preserving, researching and providing a place to broaden one's knowledge. The Langkat Regency Regional Museum is one of the legacies of the Langkat Sultanate which can still be visited today. A museum with many changes in function from a justice building to a Regional Museum. As for the problems raised in this research, the researcher took the case of inventorying existing collections in regional museum buildings using qualitative methods as a way to describe the collections in museums. There are several stages carried out to obtain the results achieved through observation, interviews and collection data collection. The aim of this research is to be able to analyze the collections in each room in the Langkat area museum building which has 6 rooms with the main room having a replica of a Malay throne or altar.